Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.energyfuels.0c00864
|View full text |Cite
|
Sign up to set email alerts
|

Extractive Catalytic Oxidative Denitrogenation of Fuels and Their Promoting Effect for Desulfurization Catalyzed by Vanadium Substituted Heteropolyacids and Molecular Oxygen

Abstract: In this contribution, we successfully apply our recently developed extractive catalytic oxidative desulfurization technology (ECODS) for the removal of different nitrogen-containing compounds (ECODN) from both gasoline and diesel fuels. Hereby, indole, 1-methylindole, 2-methylindole, 3-methylindole, quinoline, and quinaldine are completely removed from different model fuels under oxidative conditions, i.e., 120 °C and 20 bar oxygen, with the use of an aqueous HPA-5 catalyst solution within minutes. Indole and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…In particular, Keggin-type POMs ([X n+ M 12 O 40 ] (8-n)-(X: block p or d heteroatom) have been successfully used as efficient catalysts in ODS processes [31][32][33][34][35]. However, the investigation combining ODS and ODN is in a primitive stage and only one publication could be found in the literature demonstrating the ability of POMs as catalysts in this mixed systems [36].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Keggin-type POMs ([X n+ M 12 O 40 ] (8-n)-(X: block p or d heteroatom) have been successfully used as efficient catalysts in ODS processes [31][32][33][34][35]. However, the investigation combining ODS and ODN is in a primitive stage and only one publication could be found in the literature demonstrating the ability of POMs as catalysts in this mixed systems [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, water has not been used extensively as extracting agent in ODS due to the very low solubility of sulfoxides/sulfones in aqueous media. To overcome this problem, we have developed a new alternative approach for ODS called extraction‐coupled oxidative desulfurization (ECODS) ,. In this process, the sulfur contaminants in the fuel (benzthiophene, dibenzothiophene and its alkylated derivatives) are oxidized with an aqueous V−Mo−P Keggin polyoxometalate solution to water‐soluble species which are extracted in situ into the aqueous catalyst phase.…”
Section: Introductionmentioning
confidence: 99%
“…Bertleff et al suggested that a catalytic system consisting of HPA-5 (H 8 PV 5 Mo 7 O 40 ) catalyst and O 2 oxidant could remove 80% of the S-compounds (mixture of DBT, BT, and 4,6-DMDBT) from model oil (tetradecane) under reaction conditions (reaction temperature of 120 °C, reaction time 24 h, and 20 bar O 2 ).…”
Section: Homogeneous Polyoxometalatesmentioning
confidence: 99%